Flexible labour markets - Gash, V; Gash, Vanessa (2005)
﻿ This thesis investigates the quality of atypical employment to reveal whether support for the generation of temporary and part-time jobs is an effective policy for labour market renewal or whether it leads to labour market segmentation. This issue is investigated through analyses of the quality of atypical employment, with the following components of atypical work investigated: working-conditions, wages, poverty risk, exposure to unemployment and/or labour market drop out, as well as the extent to which atypical employment leads to the standard employment contract, termed its 'bridging function'. Strong and consistent variation in the quality of atypical work (relative to standard contract employment) combined with evidence of a weak bridging function is taken as an indicator of labour market marginalisation for these workers. Evidence of labour market marginalisation would suggest that non-standard contracts foster market segmentation. A key component of the analyses asserts that institutional context will structure atypical worker outcome with comparative analysis run on three countries to test this hypothesis. The countries chosen for the analysis varied in their combination of institutions thought to structure labour market outcome. The institutions thought to structure labour market outcome were classified into two groups, or axes, thought to structure labour markets in a different manner. The first group of institutions were thought to influence the relative openness or flexibility of markets, while the second was thought to influence the integration of labour market outsiders. Denmark is presented as a flexibly integrative labour market, the French market is presented as rigidly integrative and the United Kingdom is labelled flexibly non-integrative. The empirical analyses revealed strong and consistent variation in the quality of atypical work (relative to standard contract employment) and while the evidence suggests that temporary employment does provide a bridging function, the same was not true of part- time employment. This led us to conclude that policies which have sought to flexibilise the labour market through the generation of temporary and/or part-time employment are likely to contribute to market segmentation. Nonetheless we established important differences between countries which provided insights into the labour market conditions which were the most supportive of atypical worker inclusion.